Improvements in the synthesis of zeolites with low si/al ratio from venezuelan sodium silicate for an environmentally friendly process [Mejoras en la síntesis de zeolitas con baja relación Si/Al a partir de un silicato de sodio de Venezuela para un proceso ambientalmente amigable] - López Lojan, C. (2016)
LTA and FAU zeolites were successfully synthesized from a Venezuelan sodium silicate solution, by hydrothermal crystallization under autogenous pressure at 100 C, with 2 24 h crystallization times. The synthesized materials were characterized by XRD, BET specific surface area and SEM. A series of synthesis tests were performed to study the influence of the molar composition of the starting mixture over zeolites crystallization. The effect of crystallization time for a particular synthesis mixture composition was studied for both zeolites types. The reuse as alkaline medium of the mother liquor separated during filtration, and the effect of the aging before crystallization were additionally studied. The experimental results are in agreement with the crystallization mechanism proposed for zeolites synthesis in liquid phase. The use of a 2SiO2:Al2O3:6.Na2O:240H2O synthesis mixture composition allows obtaining LTA zeolite within 2 h of crystallization. For FAU zeolite, no aging period was needed when starting with a 4SiO2:Al2O3:6.6Na2O:264H2O composition. It was possible to synthesize both zeolites with high purity and crystallinity and with adequate water adsorption properties. © 2016, Revista Ingenieria e Investigacion - Editorial Board. All Rights reserved.